The Elasticity of Demand for Gambling - Suits, Daniel B. (Quarterly Journal of Economics, 1979)
The demand for gambling, 155.—Elasticity of demand, 156.—Demand for bookmaking in Nevada, 157.—Parimutuel betting, 158.—Price, tax, and state revenue, 160.